(untitled) (Scientific journal of the Fergana State University, 2023)
The article examines a critical analysis of the problem of increasing the income of the population, systematically improving the income of the population, attracting free funds, the level of paid income in a bank — the percentage should not exceed the inflation rate of the monthly minimum wage; low percentage received in the bank.